Perceived Teacher Autonomy Support and Students' Deep Learning: The Mediating Role of Self-Efficacy and the Moderating Role of Perceived Peer Support - Zhao, Jingxian; Qin, Yue (Frontiers in Psychology, 2021)
This study aims to test the mediating effect of self-efficacy on college students’ perception of teacher autonomy support and students’ deep learning, and whether the peer support perceived by students can mediate the relationship between perceived teacher autonomy support and deep learning.A survey of 1,800 college students from a provincial undergraduate normal university in Guizhou Province in China which was conducted through the revised College Student Perceived Teacher Autonomy Support Scale, Deep Learning Scale, Self-Efficacy Scale, and Peer Support Scale.(Mean age = 21 years old, SD = 1.34), Data use SPSS23.0, AMOS22.0 software for descriptive analysis and correlation analysis, exploratory factor analysis and confirmatory factor analysis, moderate effect and mediation effect analysis.The research results show that after controlling for gender, major, and grade, self-efficacy partially moderates the connection between teachers' autonomy support and deep learning of college students. In addition, perceived peer support mediates the relationship between perceived teacher autonomy support and students' self-efficacy.